Uma década de cartas dos povos indígenas ao Brasil: correspondências de 2011-2020 - Lima Costa, Suzane (Brasiliana: Journal for Brazilian Studies, 2021)
The letters that the indigenous people wrote to Brazil in the last ten years are a political and cultural translation of our present history. A translation that presents who are indigenous who write letters, while asking who is the Brazil of their correspondences, highlighting situations specific to the ethics of these writings: 1. The culture of confrontation, repetition, and courage; 2. Addressing someone who is not there and sending gestures as a policy; 3. The letter is a utopian gesture and the meaning of good living in Brazil. The way these letters are written and posted on different social networks on the Internet or published on the pages of non-governmental organizations tells of a new cultural, political and literary experiment, offered to Brazilian society by indigenous peoples as ethics for the life they want and need to have as original peoples. In this article, I intend to deal with these situations by resuming excerpts of letters written by indigenous peoples between 2011-2020 and sent to Brazil, under the name of presidents, governors, and other political authorities.